PENGGUNAAN KATA TUGAS DALAM TEKS EKSPOSISI SISWA KELAS VII SMP NEGERI 2 BUKITTINGGI - Pratami, Intan; Emidar, Emidar; Ratna, Ellya (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purpose of this research is to discribe the using of preposition and conjunction in the expotition text as class VII at SMP Negeri 2 Bukittinggi. The type of this research is qualitative research with descriptive method. The result of this research is found that the using of preposition that is states of meaning of whex a place, direction from, purpose direction, comparison, subject, and restriction. The conjunction that is which used are intra-sentence conjunction and antar-sntence conjunction. The student still can not using preposition and conjunction correctly.Â Kata kunci : kata tugas, preposisi, konjungtor